Epstein–barr virus and multiple sclerosis risk in the finnish maternity cohort. Issue 3 (3rd July 2019) - Munger, Kassandra L.; Hongell, Kira; Cortese, Marianna; Åivo, Julia; Soilu‐Hänninen, Merja; Surcel, Heljä‐Marja; Ascherio, Alberto
Abstract : Objective: To determine whether maternal Epstein–Barr virus (EBV) IgG antibody levels are associated with risk of multiple sclerosis (MS) in the offspring. Methods: We conducted a prospective nested case–control study in the Finnish Maternity Cohort (FMC) with serum samples from >800, 000 women collected during pregnancy since 1983. Cases of MS among offspring born between 1983 and 1991 were identified via hospital and prescription registries; 176 cases were matched to up to 3 controls (n = 326) on region and dates of birth, sample collection, and mother's birth. We used conditional logistic regression to estimate relative risks (RRs) and adjusted models for sex of the child, gestational age at sample collection, and maternal serum 25‐hydroxyvitamin D and cotinine levels. Similar analyses were conducted among 1, 049 women with MS and 1, 867 matched controls in the FMC. Results: Maternal viral capsid antigen IgG levels during pregnancy were associated with an increased MS risk among offspring (RRtop vs bottom quintile = 2.44, 95% confidence interval [CI] = 1.20–5.00, p trend = 0.004); no associations were found between maternal EBV nuclear antigen 1 (EBNA‐1), diffuse early antigen, or cytomegalovirus IgG levels and offspring MS risk. Among women in the FMC, those in the highest versus lowest quintile of EBNA‐1 IgG levels had a 3‐fold higher risk of MS (RR = 3.21, 95% CI = 2.37–4.35, p trend <1.11e‐16). These associations were not confounded or modified by 25‐hydroxyvitamin D. Interpretation: Offspring of mothers with high viral capsid antigen IgG during pregnancy appear to have an increased risk of MS. The increase in MS risk among women with elevated prediagnostic EBNA‐1 IgG levels is consistent with previous results. ANN NEUROL 2019;86:436–442